1996
DOI: 10.1002/(sici)1096-8628(19960823)64:3<493::aid-ajmg9>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Chondrodysplasia punctata, humero-metacarpal type: A second case

Abstract: We report on a boy with symmetrical rhizomelic shortness of the upper limbs and punctate epiphyseal calcifications noted at birth. Radiographs documented short and wide humeri, symmetrical brachymetacarpy, coronal clefts of the veretebrae, and punctate calcifications in the spine, sacrum, shoulder, feet, and trachea. Borochowitz [1991] described a similar patient with an apparently new syndrome of chondrodysplasia punctata (CP), distinct from previously described forms. He suggested the term “chondrodysplasia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…There are various types of chondrodysplasia punctata ; autosomal recessive forms (RCDP types 1, 2 and 3), X-linked dominant form (Conradi-Hünermann-Happle syndrome), an X-linked recessive brachy-telephalangic type and Sheffield type 4 . Several milder forms of CDP, tibia-metacarpal type and humero-metacarpal type, have also been described 5,6 . Within these variations, there are different syndromes characterized by distinct anomalies, severity, modes of transmission and radiological features.…”
Section: Discussionmentioning
confidence: 99%
“…There are various types of chondrodysplasia punctata ; autosomal recessive forms (RCDP types 1, 2 and 3), X-linked dominant form (Conradi-Hünermann-Happle syndrome), an X-linked recessive brachy-telephalangic type and Sheffield type 4 . Several milder forms of CDP, tibia-metacarpal type and humero-metacarpal type, have also been described 5,6 . Within these variations, there are different syndromes characterized by distinct anomalies, severity, modes of transmission and radiological features.…”
Section: Discussionmentioning
confidence: 99%
“…Fryburg and Kelly described another case of the variable form. 7 Matsui and colleagues diagnosed a newborn infant with CP-MT who was developmentally delayed at 9 months, a feature not previously associated with this disorder. 8 To classify the different forms of chondrodysplasia punctata has been difficult.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a rare ‘Humero‐Metacarpal’ form of CDP may represent a distinct entity [Borochowitz, 1991; Fryburg and Kelly, 1996]. Recently a clinical form similar to rhizomelic CDP but without the biochemical features has been described [Kumada et al, 2001].…”
Section: Discussionmentioning
confidence: 99%